ANALISIS PENCATATAN DAN PENYAJIAN LAPORAN KEUANGAN PADA UMKM BERDASARKAN SAK ENTITAS MIKRO KECIL DAN MENENGAH PADA AISYAH MART - Febi Febriani, Mardiana, dan Camelia Verahastuti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study aims to analyze the rocognition of items in financialstatements, measurement of financial statement elements, presentation ofitems in financial statements and disclosure of financial statements in AisyahMart Business are in accordance with the provisions in Micro, Small andMedium Entity Financial Accounting Standards (SAK EMKM) 2018. Theanalysis technique used in this study is a comparative descriptive method,which is a method that compares accounting treatment that includesrecognition, measurement, presentation and disclosure in Aisyah Mart andChampion method for calculating cheklist value in determining conformitycriteria. The result of the study indicate that the recognition andmeasurement of the items in the financial statements of Aisyah Mart Businessare not in accordance with SAK EMKM. Whereas the presentation anddisclosure of financial statements for Aisyah Mart Business do not match theSAK EMKM.